Impact of International Quality Improvement Collaborative on Congenital Heart Surgery in Pakistan. Issue 21 (13th April 2017) - Khan, Amina; Abdullah, Ahmed; Ahmad, Huzaifa; Rizvi, Arjumand; Batool, Sehrish; Jenkins, Kathy J; Gauvreau, Kimberlee; Amanullah, Muneer; Haq, Anwar; Aslam, Nadeem; Minai, Fauzia; Hasan, Babar
Abstract : Background: The International Quality Improvement Collaborative (IQIC) was formed to reduce mortality and morbidity from congenital heart disease (CHD) surgeries in low/middle-income countries. Objectives: We conducted this study to compare the postoperative outcomes of CHD surgeries at a centre in Pakistan before and after joining IQIC. Methods: The IQIC provides guidelines targeting key drivers responsible for morbidity and mortality in postoperativepatients with CHD. We focused primarily on nurse empowerment and improving the infection control strategies at our centre. Patients with CHD who underwent surgery at this site during the period 2011–2012 (pre-IQIC) were comparedwith those getting surgery in 2013–2014 (post-IQIC). Morbidity (major infections), mortality and factors associated with them were assessed. Results: There was a significant decrease in surgical site infections and bacterial sepsis in the post-IQIC versus pre-IQIC period (1% vs 30%, p=0.0001, respectively). A statistically insignificant decrease in the mortality rate was also noted in post-IQIC versus pre-IQIC period (6% vs 9%, p=0.17, respectively). Durations of ventilation and intensive care unit (ICU) and hospital stay were significantly reduced in the post-IQIC period. Age <1 year, malnutrition, low preoperative oxygen perfusion, Risk Adjustment for Congenital Heart Surgery score >3, major chromosomal anomalies, perfusion-related event, longer ventilation and ICU/hospital stay durations were associated with greater odds of morbidity and mortality. Conclusion: Enrolling in the IQIC programme was associated with an improvement in the postsurgical outcomes of the CHD surgeries at our centre.